2021
DOI: 10.1158/1078-0432.ccr-20-4621
|View full text |Cite
|
Sign up to set email alerts
|

Interim Analysis of the Phase II Study: Noninferiority Study of Doxorubicin with Upfront Dexrazoxane plus Olaratumab for Advanced or Metastatic Soft-Tissue Sarcoma

Abstract: To report the interim analysis of the phase II single arm noninferiority trial testing the upfront use of dexrazoxane with doxorubicin on progression free survival (PFS) and cardiac function in soft tissue sarcoma (STS). Patients and MethodsPatients with metastatic or unresectable STS who were candidates for first line treatment with doxorubicin were deemed eligible. An interim analysis was initiated after 33/65 patients were enrolled. Using the historical control of 4.6 months progression free survival (PFS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In addition to prolonging survival rates, clinicians are now increasingly concerned about complications caused by sarcoma therapy ( 20 , 23 ). Several small sample or single-center clinical cohort studies reported that antineoplastic agents such as anthracyclines increased the risk of dying from HD in sarcoma patients ( 14 , 15 ). However, due to low sarcoma incidence rates and limitations with small sample or single center studies, no robust data are available to inform clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to prolonging survival rates, clinicians are now increasingly concerned about complications caused by sarcoma therapy ( 20 , 23 ). Several small sample or single-center clinical cohort studies reported that antineoplastic agents such as anthracyclines increased the risk of dying from HD in sarcoma patients ( 14 , 15 ). However, due to low sarcoma incidence rates and limitations with small sample or single center studies, no robust data are available to inform clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, a worrisome adverse side effect is ventricular dysfunction and heart failure ( 25 ). Due to low sarcoma incidence rates, previous cardio-toxicity studies in sarcoma patients receiving chemotherapy were conducted in small sample or at single centers ( 13 15 ). In a recent comparative study of 95 patients with sarcoma, approximately 17% developed cardio-toxicity after receiving doxorubicin ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early cardiac protection permits oncologic decisions to determine when to stop or whether to reinstitute anthracycline therapy, rather than binding to some magic number. The papers by Jones et al (1) and Van Tine et al, (2) substantiating the known cardioprotective effect of this agent and emphasizing that the antitumor activity of dexrazoxane-protected doxorubicin against adult sarcomas is not impaired when dexrazoxane is started with course 1, lend further support to the routine use of dexrazoxane in sarcomas, or wherever there may be potential benefit from giving additional doxorubicin at some point in time. Although Jones et al (1) did not demonstrate specifically the effects of dexrazoxane from day 1, since the time of initiation was left at the investigator's discretion, the study of Van Tine et al optimized cardiac protection by routinely starting dexrazoxane at day 1.…”
mentioning
confidence: 87%
“…In this issue of Clinical Cancer Research, Jones et al (1) and Van Tine et al (2) question the traditional maximum lifetime cumulative dose of doxorubicin and lend support to protecting against doxorubicin cardiac toxicity by initiating dexrazoxane prior to the first anthracycline dose in patients with soft-tissue sarcomas. Is it time to re-evaluate the maximum lifetime dose of doxorubicin?…”
mentioning
confidence: 99%
“…Dexrazoxane is the only drug currently approved by the FDA that provides protection against Dox-induced cardiotoxicity. However, dexrazoxane not only causes side effects, such as hematological toxicity and myelosuppression, but also decreases the antitumor efficacy of Dox ( 11 , 12 ). For instance, the activation of hypoxia-inducible transcription factor, an oncogene, may contribute to the protective effect of dexrazoxane against anthracycline cardiotoxicity in dexrazoxane-treated H9c2 cardiomyocytes ( 13 ).…”
Section: Introductionmentioning
confidence: 99%